SOME STRATEGIES TO ENHANCE THE EFFICACY OF BORDER SERVICE TRAINING - Lkhagva, Lkhagvasuren (International Journal of Innovative Technologies in Social Science, 2026)
This study examines the implementation and outcomes of a military training program conducted at the Border Service School of the University of Internal Affairs in partnership with a client organization from 2018 to 2020. The primary objective is to evaluate the effectiveness of the existing training structure and recommend ways to enhance cadet learning outcomes. Despite limitations in scope and resources, the study identifies areas for improvement in content delivery and instructional methods. A key focus of the research is the utilization of reflex-based training, a method commonly utilized in military vocational education systems in Russia and China. The approach emphasizes repetitive, scenario-based training involving officers and sergeants to deepen their understanding of operational conditions and enhance their performance. The report highlights initial findings and progress in developing and refining professional competency programs for military officers under the mentorship of experienced instructors at the Border Service School. A comparative analysis of training methodologies employed in similar institutions in Russia and China demonstrates that integrating associative-reflex methods with modern technologies, such as artificial intelligence and virtual simulation environments, significantly enhances training outcomes. The results suggest that the current infrastructure and pedagogical approaches at the Border Service School necessitate modernization, and the study recommends a comprehensive framework incorporating smart classrooms, virtual laboratories, augmented reality training environments, and intelligent management systems to align with international standards in military border service education.